THE INFLUENCE OF ENVIRONMENTAL RESOURCES ON STUDENTS PERFORMANCE IN BIOLOGY - Matazu, Suleiman Sa’adu (Sokoto Educational Review, 2020)
This study was designed to investigate the influence of environmental resources on students’ performance in Biology. It adopted the use of simple random sampling technique to select one hundred and sixty (160) senior secondary one (SSI) students from four (4) secondary schools in Matazu Local Government Area of Katsina State. Biology Achievement Test (BAT) was used as an instrument to gather the data for study. Similarly, independent t-test was used to analyze the data collected. The results showed that students taught using ecological garden performed significantly better than those students taught without ecological garden. It has also been observed that students in a small class size taught using ecological garden performed significantly better than those students in the large class size. Based on that, conclusions were drawn and recommendations were made among which include teachers should teach concepts in Biology using environmental resources for better performance.